Microbial co-occurrence patterns in deep Precambrian bedrock fracture fluids - Purkamo, Lotta; Bomberg, Malin; Kietäväinen, Riikka; Salavirta, Heikki; Nyyssonen, Mari; Nuppunen-Puputti, Maija; Ahonen, Lasse; Kukkonen, Ilmo; Itavaara, Merja (Biogeosciences, 2016)
The bacterial and archaeal community composition and the possible carbon assimilation processes and energy sources of microbial communities in oligotrophic, deep, crystalline bedrock fractures is yet to be resolved. In this study, intrinsic microbial communities from groundwater of six fracture zones from 180 to 2300aEuro-m depths in Outokumpu bedrock were characterized using high-throughput amplicon sequencing and metagenomic prediction. Comamonadaceae-, Anaerobrancaceae- and Pseudomonadaceae-related operational taxonomic units (OTUs) form the core community in deep crystalline bedrock fractures in Outokumpu. Archaeal communities were mainly composed of Methanobacteriaceae-affiliating OTUs. The predicted bacterial metagenomes showed that pathways involved in fatty acid and amino sugar metabolism were common. In addition, relative abundance of genes coding the enzymes of autotrophic carbon fixation pathways in predicted metagenomes was low. This indicates that heterotrophic carbon assimilation is more important for microbial communities of the fracture zones. Network analysis based on co-occurrence of OTUs revealed possible "keystone" genera of the microbial communities belonging to Burkholderiales and Clostridiales. Bacterial communities in fractures resemble those found in oligotrophic, hydrogen-enriched environments. Serpentinization reactions of ophiolitic rocks in Outokumpu assemblage may provide a source of energy and organic carbon compounds for the microbial communities in the fractures. Sulfate reducers and methanogens form a minority of the total microbial communities, but OTUs forming these minor groups are similar to those found in other deep Precambrian terrestrial bedrock environments. Peer reviewed